Efficient multiscale methodology for local stress analysis of metallic railway bridges based on modal superposition principles - Horas, Cláudio (2022)
This paper presents an advanced submodelling methodology for local stress analysis of complex details of existing metallic railway bridges. The fatigue assessment of connections of large structures based on local methods leads inherently to a multiscale problem that can only be solved by adopting efficient numerical procedures. Aiming to overcome such limitations that influence the analysis process, submodelling techniques and modal superposition principles are combined to fully represent numerically the local geometrical, material and contact properties of the fatigue-critical details. The results of experimental in situ tests are proposed to characterise the numerical models and respective multiscale relation, implementing optimisation and validation procedures. In this work, the suggested efficient multiscale methodology for stress analysis aims to allow the subsequent local fatigue assessment, according to the real mechanism of loading transference, reducing sources of conservatism. All numerical procedures and respective validation thru experimental techniques are illustrated using a real case study.